Viability of different feed rates for Astyanax bimaculatus culture - Jatobá, Adolfo (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to evaluate the growth performance and cost of Astyanax bimaculatus (yellow tail lambari) fed with different feeding rates. For such, 720 (4.06 ± 0.33 g) juvenile fish were fed with four different feeding rates (2.5, 4.0, 5.5, and 7.0% of biomass). After six weeks, growth performance and cost of the fish produced (in kg) were evaluated. Fish fed with 4.0 and 5.5% of the biomass showed the best growth performance and financial results; thus, these feed rates are the most attractive for Astyanax bimaculatus culture.